BEHAVIORAL ACCOUNTING AS A CATALYST IN THE ORGANIZATIONAL TRANSFORMATION PROCESS TOWARD SUSTAINABILITY - Dayani, Ni Wayan Yellow Prinsis; Budiasih, I Gusti Ayu Nyoman (UI Scholars Hub, 2024)
This research investigates the role of behavioral accounting as a catalyst in the organizational transformation process towards sustainability using phenomenological methods. The study aims to explore how behavioral accounting identifies individual behavioral factors, designs efficient sustainability systems, and enhances organizational commitment to sustainable practices. The research employs observation, secondary data analysis, and semi-structured interviews with organizational internal team, analyzed through Interpretative Phenomenological Analysis (IPA). Findings indicate that behavioral accounting contributes to organizational sustainability by enhancing transparency in accounting information, thereby minimizing the risk of fund misuse and ensuring efficient resource allocation. This research supports behavioral accounting as pivotal in shaping a sustainable organizational culture, offering both theoretical insights and practical implications.